The richness and abundance of epigaeic mountain beetles in north-western Patagonia, Argentina: assessment of patterns and environmental correlates - Werenkraut, Victoria (2014)
Aim: Our aims were: (1) to study the shape of the species richness–elevation and abundance–elevation relationships (SRER and AER, respectively) in epigaeic mountain beetles; and (2) to analyse how richness and abundance of the beetles vary across the full gradient and within the forests and steppes in association with environmental variables representing productivity, thermal limitation, water–energy dynamics, environmental heterogeneity and soil characteristics. Location: Five mountains at temperate latitudes in north-western Patagonia, Argentina. Methods: We collected beetles using 486 pitfall traps arranged in fifty-four 100 m² grid plots of nine traps, established at intervals of about 100 m of elevation from the base to the summit of each mountain. We used multi-model selection and the Akaike information criterion to find the best ecological explanation for species richness and abundance variation. Results: The AER was hump-shaped in four mountains and negative in one; the SRER was negative in one case, humped in two cases, and either low-plateau or humped in the remaining two. Across the full gradient, the increase in vegetation cover, mainly associated with the presence of forests, predominately accounted for SRERs and AERs. In the forests, energy variables combined with precipitation, soil attributes and environmental heterogeneity accounted for richness and abundance. In the steppes, potential evapotranspiration and plant productivity were important. Main conclusions: We confirmed different forms in the shape of SRERs, and the predominance of hump-shaped patterns in AERs. Vegetation type (forests versus steppes) accounted for most of the variation in species richness and abundance on all mountains. Associations with local environmental factors were rather more variable and changed with the spatial extent of analysis, thus confirming the spatial dependence of the species richness/abundance–environment relationships.